The Economics of Mobile Telephone Regulation - Justus Haucap (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
This paper analyzes how competition works in mobile telecommuncations markets and, bases on this analysis, we discuss whether regulatory intervention in mobile telephone markets is justified from an economic perspective. Starting point of our analysis is the observation that an evaluation of regulatory interventions into mobile telecommunications markets cannot be made without a deeper understanding for competitive processes in mobile telephony. What is of decisive relevance for understanding competition in mobile telephony, is the fact that building a mobile telephone network requires highly specific investments, which take place under significant uncertainty, as investments in 3G networks such as UMTS illustrate. An inevitable consequence of specific investments are sunk costs. Hence, one can only expect firms to extensively invest and innovate if firms can hold a justified expectation to work profitably after they have invested. To cover their capital costs, which are largely fixed and not avoidable, firms need to follow a pricing policy that involves prices above incremental costs. Hence, a key determinant for mobile operators' price policy lies in their cost structure, which is characterized by high fixed and common costs that are also sunk and relatively low incremental costs. In such situations, efficiency demands so-called Ramsey pricing structures, which involves different mark-ups for different services. In contrast, a situation with uniform mark-ups will generally be inefficient. Instead, services with an inelastic demand should carry relatively high prices, while services, for which the demand is rather elastic, should be priced close to marginal costs. Exactly such a pricing structure results when unregualted firms are left to maximize their profits. Hence, the factor that prices and mark-ups differ between different services and markets is an efficiency imperative and not a sign for market failure. Nevertheless the necessity of interconnection and fixed-to-mobile termination may give rise to competition problems. As we argue in this paper, closer analysis shows that these problems do not automatically imply that sector specific regulation is warranted. The same hold for the question of regulated mobile number portability. Instead, an ex post introduction of sector specific reguation can be regarded as a brech of the implict regulatory contract by the State. This Government hold-up socializes and redistributes operators' profits, while the operators carried the initial investment risk. Such a Government hold-up reduces firms' incentives for investment and innovation and, thereby, also harms consumers in the long run. In addtion, there is a real risk of regulatory failure, as empirical evidence demonstrates. Based on these considerations, this paper fiercely advises against sector specific regulation of mobile telephone markets. The social welfare loss that would arise from such regulations are estimated to be enormous.
urn:nbn:de:gbv:705-opus-1326
Keywords: K21; L96; L51; L13; 330; Mobile telephony; Competition; Regulation; Interconnection; Call Termination; Number Portability; Roaming; Mobilkommunikation; Regulierung; Telekommunikationspolitik; Wettbewerb; Markteintritt; Theorie